Discovery Learning Research in Mathematics Learning (1968-2023): A Bibliometric Review - Ilham Muhammad; Dadang Juandi (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
The aim of this research is to identify research developments related to Discovery Learning in mathematics learning. This research uses a bibliometric analysis method by collecting data from the Scopus database. The data is then saved in two formats, namely CSV and RIS. Data in CSV format was analyzed using VOSviewer, while data in RIS format was analyzed using Harzing's Publish or Perish software. This research refers to 72 research sources regarding discovery learning in mathematics learning from 1968 to 2023. The research results show that the number of publications related to discovery learning in mathematics learning continues to increase every year. Publications in 2012 had more than 130 citations, this number exceeds publications in other years. The majority of these publications were found in Q2 category journals, with a total of 28 publications. The focus of this research covers three main areas: 1) learning outcomes, learning environments, and the role of universities; 2) technology and STEM (Science, Technology, Engineering, and Mathematics); 3) problems in teaching mathematics. New themes that emerge in research regarding discovery learning in mathematics learning include STEM, communication, self-confidence, learning activities, creativity, critical thinking, and efficacy. However, the term